(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The three main religions indicate that each person has a destiny in life based on their actions and beliefs. Judaism considers that man tests his existence in this life and must perform religious duties to prove his loyalty to God. Whoever does so successfully deserves to enter the afterlife (paradise), while those who do not will burn in hell. Christianity believes that man was created to live with God forever, and that faith in Christ frees man from sin and makes him worthy of eternal life. Those who do not believe in Christ will burn in hell. Islam believes that man achieves his destiny through faith and good deeds, and that he will be held accountable for his actions in this life and receive what he deserves in the afterlife. Faith in God and His Messenger and performing good deeds qualifies man to enter paradise, while unbelievers will enter hell for their disbelief and disobedience.